(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
Collective violence is a crucial phenomenon in order to understand the process of Mexican independence and its social dimension. But there is not a comprehensive study on the topic because the existing works are partial, due to the particular aspects they analyze or because of the polarized visions with which they attack or defend independent or royal violence. The purpose of this paper is to approach the topic of collective violence during the Mexican Independence War, by characterizing this phenomenon and making the distinction between subversive violence and repressive violence. After analyzing the two categories, an evaluation of the two categories and its underlying meaning of violent acts that can be observed is offered.